Advances in Cholesteric Liquid Crystals - Mitov, Michel (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
With their helical structure, cholesteric liquid crystals figure prominently in liquid crystal science. The selective reflection of light is their flagship property, and they offer a myriad of applications as advanced optical materials with multiscale properties. The cholesteric structure is also a ubiquitous design in the animal and plant kingdoms. This book contains eight contributions on fundamental investigations about defects, textures and structures of cholesteric materials, and experimental studies aimed at applications such as temperature sensors, head-up displays for improving automobile driving safety, or smart windows.